Consumers' perception of corporal social responsability as key to sucessful relationships with grocery retailers - Filipe, Sandra Sarabando (2017)
Nowadays, it is fundamental to build long-term relationships with stakeholders and to win customers’ loyalty is viewed as a priority by many organizations. However, it is not enough to implement a loyalty program; it is necessary something more consistent to create, maintain and sustain a solid base of loyal customers. The main purpose of the current thesis was: (i) to characterize and analyse the socially responsible consumer behavior in the Portuguese context; (ii) and to examine the possible effects of socially responsible consumer behavior, store format, loyalty programs and consumers’ Perception of Corporate Social Responsibility on the relationship between grocery retailers and consumers. In order to address the purpose of this thesis, in an exploratory phase, data were collected and qualitatively analyzed from a focus group and interviews with managers and heads of marketing departments of grocery store. In a second phase, two online surveys, with 988 and 618 valid responses obtained among Portuguese customers were analysed by means of quantitative statistical techniques, namely Structural Equation Modelling. Results provided clear evidence that socially responsible behaviors are well established among consumers and the strongest effects from psychological factors on these behaviors were obtained for perceived consumer effectiveness, perception of altruist motivations for CSR held by companies and collectivism. Moreover, results suggested that the socially responsible consumer is more likely to be females, elder, with a professional occupation, and with at least one child in the household. In addition, results showed that consumers’ perceptions of Corporate Social Responsibility is determinant for successful relationships between grocery retailers and their customers mainly through more positive satisfaction, trust and loyalty. Results also suggested that supermarkets lead to higher levels of customers’ trust and loyalty (indirectly) and that loyalty programs’ membership do not show higher levels of customers' loyalty.